Astigmatism in relation to length and site of corneal lacerations - Atti, Srihari; Killani, Srinivas Prasad; Gupta, Atul; Pujala, Sambasiva Reddy; Sridhar, Goli; Mahendra, Superna (International Journal of Research in Medical Sciences, 2016)
Background: Corneal lacerations are the common cause of astigmatism that can prevent a good visual outcome. This was to evaluate Astigmatism in relation to the Length and Site of Corneal Lacerations. Methods: This was a study in the Cornea clinic, Sarojini Devi Eye Hospital and Regional Institute of Ophthalmology, Osmania Medical College, Hyderabad over a period from August 2012 to April 2014. The study group was 25 Patients of corneal lacerations. The data of age and sex, the length of corneal lacerations in terms of corneal diameter of <1/3rd and >1/3rd and the site of the laceration in the cornea either central or peripheral was noted. All the corneal lacerations were sutured with interrupted 10-0 mono filament nylon. Suture removal was done over a period of 6 -12 weeks following surgery. Astigmatism (Diopters) was estimated by Keratometer after sutures removal. Results: Our study age distribution was 11(44.0%) in >10 -20 yrs, 11 (44.0%) in 21 – 30 yrs and 3(12.0%) in 31 -40 yrs. Sex distribution was 17(68.0%) of males and 8(32.0%) of females. The length of Corneal laceration in terms of corneal diameter was < 1/3rd in 4(16.0%) and >1/3rd in 21(84.0%). The site of Laceration in the cornea was peripheral in 6(24.0%) and central in 19(76.0%). The Astigmatism in relation to Length and Site of Corneal Laceration showed < 2.0 D in 3(12.0%), 2 – 4.0 D in 11(44.0%), 4- 6.0 D in 4(16.0%), > 6.0D in 4(16.0%) and irregular astigmatism in 3(12.0%). The astigmatism in peripheral corneal lacerations of < 1/3rd and > 1/3rd of corneal diameter was < 2.0 D in 12.0% and 2-4.0 D in 12.0% respectively. The Astigmatism in central corneal lacerations of <1/3rd and >1/3rd of corneal diameter was 2- 4.0D in 4.0% and 2-4.0D in 28.0%, 4-6.0D in 16.0%, >6.0D in 16.0% and irregular Astigmatism in 12.0% respectively. Time of sutures removal was 80.0% at 6-8 wks, 12.0% at 8-10 wks and 8.0% at 10 -12 wks. Conclusions: The corneal astigmatism depends upon the length and site of corneal laceration. Severity of astigmatism was directly proportion to the length of corneal laceration. The wound was nearer to the centre of the cornea, the greater was the astigmatism.